Assessment of Relational Risks Associated with Public Infrastructure Projects in Edo and Delta States - Oso, Sunday Benedict; Ajator, Uchenna Obiekwe (International Journal of Independent Research Studies, 2025)
Infrastructure projects in Nigeria, particularly in Edo and Delta States, are frequently plagued by relational risks that compromise project success. This study assesses relational risks associated with public infrastructure projects. It identified relational risks and establishes the mitigating measures to minimize relational risks associated with public infrastructure projects in the study area. The study employed a quantitative survey research design and stratified random sampling technique was employed in reaching the 268 respondents to whom the questionnaires were distributed, 202 questionnaires were duly completed and returned. Data collected were analysed using statistical tools such as SPSS Version 23 Applications. The findings show that the top most frequently occurring relational risks associated with infrastructure projects are misappropriation of resources and information, distortion of information and cutting corners. Furthermore, the results reveal that the most effective relational risks mitigation strategies are encouraging clear communication channels and regular updates. The study contributes to the growing of body of knowledge on relational risks in developing economies and provides actionable strategies for policy makers, contractors and construction professionals in Edo and Delta States.